Emerging enantiomeric resolution materials with homochiral nano-fabrications. Issue 28 (29th June 2015) - Wang, Huai-Song; Wei, Ji-Ping
Abstract : Advanced materials with precise homochiral fabrication at nanoscale have been proven to be effective in improvement of the selectivity and efficiency of enantio-resolution. Abstract : The major scientific challenge of enantiomeric separation is to develop simple, rapid, and sensitive routine analytical methods. Generally, enantio-resolution is still based on "three-point interaction" theory, which indicates that homochiral sites are needed for enantio-selective interaction. However, in recent years, advanced materials with precise homochiral fabrication at the nanoscale have been synthesized, and have shown great potential in development of high-throughput enantio-resolution methods. This tutorial review summarizes fabrication and applications of homochiral materials for enantio-selective recognition and separation. These materials, which include intrinsic and restructured chiral metal surfaces, plasmonic nanostructures, coordination polymers, organic polymer sensors, and molecularly imprinted polymers, have been applied as sensors or chiral stationary phases (CSPs) for efficient enantio-resolution.